Study on the significance correlation between CEBPA and Calreticulin at mRNA level diagnosed in de nevo AML patients (Bangladesh Journal of Medical Science, 2020)
Objectives: Calreticulin (CALR) and CCAAT/enhancer binding protein (C/EBP) alpha (CEBPA) are two important multifunctional proteins which play different roles in regulation of hematopoiesis. Expressional changes of these genes were related to the malignancy.Methods: The present study aimed to investigate the expression levels of CALR and CEBPA genes in 96 de novo AML patients compared to 18 normal people as the control group through the Real-Time-PCR.Results: Results of the present study revealed that the expression of these genes was significantly higher in patients with AML than the normal group (P